2010
DOI: 10.1016/j.quascirev.2009.11.024
|View full text |Cite
|
Sign up to set email alerts
|

A combined oxygen and silicon diatom isotope record of Late Quaternary change in Lake El'gygytgyn, North East Siberia

Abstract: Determining the response of sites within the Arctic Circle to long-term climatic change remains an essential pre-requisite for assessing the susceptibility of these regions to future global warming and Arctic Si data from Lake El'gygytgyn, Russia, and suggest environmental changes that would have impacted across West Beringia from the Last Glacial Maximum to the modern day. In combination with other records, the results raise the potential for climatic teleconnections to exist between the region and sites in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
57
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 72 publications
(70 citation statements)
references
References 123 publications
5
57
2
Order By: Relevance
“…van Bennekom et al, 1989). Previous work has shown diatom Al 2 O 3 concentrations for Lake Baikal of 0.15 wt.% (Swann, 2010). Such concentrations are closer to those of PS1772-8 (Al 2 O 3 = 0.09 wt.%) than BFC (Al 2 O 3 = 2.0 wt.%) and may explain why residual values are significant lower for the PS1772-8-"Silt" model than BFC mod -"Silt".…”
Section: Diatom End-membermentioning
confidence: 57%
See 1 more Smart Citation
“…van Bennekom et al, 1989). Previous work has shown diatom Al 2 O 3 concentrations for Lake Baikal of 0.15 wt.% (Swann, 2010). Such concentrations are closer to those of PS1772-8 (Al 2 O 3 = 0.09 wt.%) than BFC (Al 2 O 3 = 2.0 wt.%) and may explain why residual values are significant lower for the PS1772-8-"Silt" model than BFC mod -"Silt".…”
Section: Diatom End-membermentioning
confidence: 57%
“…Increased attention is focused on the potential for geochemical measurements of biogenic silica to be used in palaeoenvironmental research in both continental, riverine, lacustrine and marine settings (e.g., Filippelli et al, 2000;de la Rocha et al, 2000;de la Rocha, 2003de la Rocha, , 2006Derry et al, 2005;Hendry and Rickaby, 2008;Hodson et al, 2008;Opfergelt et al, 2008;Swann et al, 2010). These studies, most commonly involving the analysis of diatoms, plant phytoliths, radiolaria and siliceous sponges, are believed to be particularly important in attempts to better understand the global silicon cycle as well as high latitude environmental change in regions where carbonates are not readily preserved in the sediment record (Conley, 2002;Street-Perrott and Barker, 2008;Leng et al, 2009;Swann and Leng, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Although being yet few, oxygen isotope archives available from Russia (Chapligin et al, 2012à;Jones et al, 2004;Meyer et al, 2015;Swann et al, 2010) extend the knowledge of global change, lake hydrology, and atmospheric circulation that controls moisture inputs. Specifically, δ 18 O diatom data from Lake Baikal revealed general trends in the system responses to global change (Kalmychkov et al, 2007;Mackay et al, 2008Mackay et al, , 2011Mackay et al, , 2013Morley et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The 175 m deep, 12 km wide lake lies inside a 3.6 million year old meteorite impact crater that is 18 km wide and has presumably been filling with sediments since the time of the impact. The impact, the crater, the sediment core, and the physical environment are all well-described in a series of prior papers (Belya and Chershnev, 1993;Glushkova, 1993;Layer, 2000;Nowaczyk et al, 2002;Nolan et al, 2003;Cherapanova et al, 2007;Glushkova and Smirnov, 2007;Melles et al, 2007;Minyuk et al, 2007;Nolan and Brigham-Grette, 2007;Brigham-Grette, 2009;Swann et al, 2010) and those found in this special issue (Melles et al, 2012;Minyuk et al, 2013).…”
Section: Introductionmentioning
confidence: 73%